The influence of Brand Awareness and Consumer Trust on the Purchase Decision of Maybelline Superstay Matte Ink Products among Instagram Social Media Users - Chanissa Purwaningrum (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
The Covid-19 pandemic has had a significant impact on the cosmetics industry. Since the mandatory use of masks while traveling and the increased time spent indoors, the use of cosmetic products has shifted. The use of masks to comply with health protocols while working has led people to prefer using skincare products only, or focusing primarily on eye makeup and transfer-proof matte lip products. One of Maybelline New York's flagship products is their lip cream, Maybelline Superstay Matte Ink, which has become a favorite among many people. When deciding to purchase this matte lip product, consumers consider factors that make them want to buy it. There are several factors that influence repeat purchase decisions, such as brand awareness and consumer trust in the brand. In the cosmetics industry, there are numerous emerging brands, ranging from well-known brands to unknown ones. This is where brand awareness plays a strong role in influencing consumers' repeat purchase decisions. In this proposal, the author discusses the analysis of brand awareness and consumer trust in the purchasing decisions of Maybelline Superstay Matte Ink products among Instagram social media users, using a quantitative analysis method with statistical tests where Brand Awareness is the X1 variable, Consumer Trust is the X2 variable, and Product Purchase Decision is the Y variable. The research will be conducted among the residents of Jakarta on the Instagram social media platform.